(untitled) (The Chittagong University Journal of Science, 2023)
Menopause is the upper bound of the female reproductive span. Considering the importance of this demographic event in the context of reproductive process and fertility, the prime objective of this research work is to investigate thoroughly the current scenario of age at menopause and also to identify the significant covariates of this last segment of human reproductive span among adult married women in an urban area of Bangladesh. This research work was based on the primary data, collected by direct field investigation through a well-structured interview schedule. In this study, a sample of 234 married women aged 40-55 years was interviewed; out of them, 113 respondents reported that they reached the menopausal stage at the time of the interview. The results show that the overall mean age at menopause among the studied women is 47.07±3.35 years with substantial variations by the respondents’ background characteristics. The coefficient of variation (7.1%) indicates extreme heterogeneity in age at menopause of the respondents. The coefficient of skewness (ɣ= -0.58) and excess of kurtosis (ɣ= -0.86) reflect that the shape characteristics of menopausal age are negatively skewed and platykurtic. Findings from multivariate Cox-proportional hazard analysis demonstrate that respondents’ current age, BMI, husbands’ occupation, use of contraception, exercising habit, and presence of disease significantly influence the age at menopause. Based on the findings of this study, it can be concluded that awareness regarding the aforementioned issues should be taken into cognizance for the natural age at menopause. The Chittagong Univ. J. Sci. 44(1): 63-84, 2022